Multidomain sumoylation of the ecdysone receptor (EcR) from Drosophila melanogaster. - Seliga, J.; Bielska, K.; Wieczorek, E.; Or?owski, M.; Niedenthal, R.; O?yhar, A. (Journal of Steroid Biochemistry and Molecular Biology, 2013)
The 20-hydroxyecdysone receptor (EcR) is a transcription factor belonging to the nuclear receptor superfamily. Together with the ultraspiracle nuclear receptor (Usp) it coordinates critical biological processes in insects such as development and reproduction. EcR and its ligands are used in commercially available ecdysone-inducible expression systems and are considered to be artificial gene switches with potential therapeutic applications. However, the regulation of EcR action is still unclear, especially in mammals and as far as posttranslational modifications are concerned. Up until now, there has been no study on EcR sumoylation. Using bioinformatic predictors, a Ubc9 fusion-directed sumoylation system and mutagenesis experiments, we present EcR as a new target of SUMO1 and SUMO3 modification. Our research revealed that EcR undergoes isoform-specific multisumoylation. The pattern of modification remains unchanged in the presence of the ligand and the dimerization partner. The SUMO acceptor sites are located in the DNA-binding domain and the ligand-binding domain that both exhibit structural plasticity. We also demonstrated the existence of a sumoylation site in the F region and EcRA-A/B region, both revealing characteristics of intrinsically disordered regions. The consequences of modification and the resulting impact on conformation and function may be especially crucial for the disordered sequences in these two areas. The isoform-specificity of sumoylation may explain the differences in the transcriptional activity of EcR isoforms.